2015
DOI: 10.1089/sur.2014.187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MDR-Acinetobacter baumannii in Orthopedic Surgical Site Infections

Abstract: Staphylococcus aureus was the main causative organism of orthopedic SSI (44.4%), whereas A. baumannii represented only (16.67%) of the causative organisms. MDR Acinetobacter CHROMagar reduced the turnaround time for screening of MDR-AB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…Among the etiologies, S. aureus was the most common constituting 37% of the overall isolates. This is in agreement with previous studies in Italy [25],Iran [26], Saudi Arabia [21], Egypt [27] and Kenya [28]. Similarly, previous studies in different parts of Ethiopia had also reported S. aureus as the most frequent isolate from SSIs [19,20,29].…”
Section: Discussionsupporting
confidence: 92%
“…Among the etiologies, S. aureus was the most common constituting 37% of the overall isolates. This is in agreement with previous studies in Italy [25],Iran [26], Saudi Arabia [21], Egypt [27] and Kenya [28]. Similarly, previous studies in different parts of Ethiopia had also reported S. aureus as the most frequent isolate from SSIs [19,20,29].…”
Section: Discussionsupporting
confidence: 92%
“…Invasive blood infection was detected among few percentage (6%)of hospitalized cancer patients during the 6-month study period ( Table 2). The rest of the isolates can be considered colonizers and might become potential pathogens for patients under certain condition, especially in association with the use of invasive procedures [23][24]. There is no significance difference in general demographic characteristics between male and female patients or their ages, whereas treatment with antibiotics showed increased significantly the chance of (P=0.033) colonization with A. baumanni.…”
Section: Discussionmentioning
confidence: 97%
“…It is speculated that the axillary and inguinal skin sites, which are moist and rich in apocrine glands, may represent microbial niches that are particularly favorable for long-term colonization with MDROs. 4,8 CHG bathing can decrease the bioburden of bacteria and yeasts on patients, the hospital environment, and the hands of health care workers. 29 Our study demonstrated that the implementation of CHG decolonization policy was associated with significant reduction of overall risk of surgical site infection after surgery in the SICU from 24% to 15%.…”
Section: Discussionmentioning
confidence: 99%
“…All SSI cases had drained pus from the deep incision in addition to one or more of the following criteria: 1) A deep incision that impulsively dehisced or is purposely opened by a surgeon and was culture-positive; and 2) plus one of the following signs or symptoms: fever (>38°C), localized pain, or tenderness. 4,6 Causative organisms of SSI were predominated by gram negative MDROs as shown by the unit antibiogram and phase I collected data. Therefore, screening for colonization with OXA-48-type (CPE) and screening for colonization with A. baumannii using Chromagars were done according to the manufacturer's instructions as shown in Figures 1 and 2 respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation